Heavy metals in barnacles Balanus sp.: from biomonitoring to coastal management - Yap, Chee Kong; Wing, Sam Lo; Nulit, Rosimah; Ibrahim, Mohd Hafiz; Yap, Chee Wah; Sharifinia, Moslem; Bakhtiari, Alireza Riyahi; Al Shami, Salman Abdo (Biomedgrid, 2020)
This study determined the levels of Cd, Cu, Fe, Ni, and Zn in the soft tissues and shells of barnacles (Balanus sp.) collected from the Kuala Juru, Sebatu, Sg. Ayam and Kg. Pasir Puteh, Peninsular Malaysia, obtained in 2008. The metal concentrations (μg/g dry weight) in the soft tissues of Balanus sp. received from four sites in Peninsular Malaysia ranged from 2.93-4.17 for Cd, 20.2-92.5 for Cu, 480-1193 for Fe, 6.40-18.0 for Ni, and 224-414 for Zn. Based on the present data, the trace metal bioavailability’s to the Balanus in all the populations, especially in a known polluted site at Kg. Pasir Puteh is low. Overall, this preliminary baseline data can be used for regular ecological monitoring for the effective management of the coastal area in Malaysia.